Analysis of hip joint cross-shear under variable activities using a novel virtual joint model within Visual3D. (October 2021) - Layton, Robin B; Messenger, Neil; Stewart, Todd D
Cross-shear forces occur between bearing surfaces at the hip and have been identified as a key contributor to prosthesis wear. Understanding the variation in relative motion paths between both individuals and activities, is a possible explanation for increased revision rates for younger patients and could assist in improved pre-clinical testing regimes. Additionally, there is little information for the pre-clinical testing of cartilage substitution therapies for younger more active individuals. The calculation of motion paths has previously relied on computational modelling software which can be complex and time-consuming. The aim of this study was to determine whether the motion paths calculations could be integrated into gait analysis software to improve batch processing, reduce analysis time and ultimately improve the efficiency of the analysis of cross-shear variation for a broader range of activities. A novel Virtual Joint model was developed within Visual3D for calculating motion paths. This model was compared to previous computational methods and found to provide a competitive solution for cross shear analysis (accuracy <0.01 mm error between methods). The virtual hip model was subsequently applied to 13 common activities to investigate local aspect ratio's, velocities and accelerations. Surprisingly walking produced the harshest cross shear motion paths in subjects. Within walking, of additional interest was that the localised change in acceleration for subjects was six times greater compared to the same point on an equivalent smoothed simulator cycle. The Virtual hip developed in Visual 3D provides a time saving technique for visualising and processing large data sets directly from motion files. The authors postulate that rather than focussing on a generalised smoothed cross-shear model that pre-clinical testing of more delicate structures should consider localised changes in acceleration as these may be more important in the assessment of cartilage substitutes sensitive to shear.